2019
DOI: 10.1021/acsanm.9b02064
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healable Lanthanoid-Based Metallogels: Dye Removal and Crystallization in the Confined Gel State

Abstract: The self-healing property of metallogels resembles the innate self-healing of plant and animal biomaterials, making metallogels potential candidates for detailed studies. Tetrazoles with diverse coordination abilities and extensive H-bond formation capabilities may be able to be used as ligands to generate metallogels. In this report, four metallogels (M1G6Cl, M2G6Cl, M1G6NO 3 , and M3G6NO 3 ) based on different lanthanoids and functionalized with di­(1H-tetrazole-5-yl)­methane (H 2 G6) are designed and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…Plant and animal biomaterials show an intrinsic natural self-healing property. Metallogels are found to be potential candidates, which can mimic such kinds of properties . Tetrazole, with four electronegative N-atoms in the ring, is one of the probable candidates that might show an inherited self-healing property as it tends to form coordinate covalent bonds with metal centers and is also open for extensive hydrogen bonding .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant and animal biomaterials show an intrinsic natural self-healing property. Metallogels are found to be potential candidates, which can mimic such kinds of properties . Tetrazole, with four electronegative N-atoms in the ring, is one of the probable candidates that might show an inherited self-healing property as it tends to form coordinate covalent bonds with metal centers and is also open for extensive hydrogen bonding .…”
Section: Resultsmentioning
confidence: 99%
“…Introduction of metal ions in a gel network influences several properties including gel strength and morphology. A metal-containing gel can also show additional qualities such as optical properties, magnetic properties, sensing, catalysis, , conductivity, self-healing properties, , etc. Apart from that, as per literature reports, metallogels can show the tendency to stabilize nanoparticles of the same metals in the gel matrix to obtain different nanocomposites, which are generally formed by different covalent and noncovalent interactions between supramolecular soft materials and multidimensional nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…The material can be stretched to 21 times its initial length of a loading rate of 100 mm Min without cracking, and can lift 2250 without cracking, 6,400 times its own weight, these excellent properties make the material's range of optical and mechanical applications significantly improved. At the same time, Novina Malviya [77] and others had found that lanthanide ions (Ln 3+ ) could be used as self-healing materials, and metal coordination bonds were formed between lanthanide ions (Ln 3+ ) and the complexes, which make the self-healing materials have unique properties such as luminescence. We had studied the luminescent properties of the material for the following reasons: The unique luminescent properties of lanthanide ions (Ln 3+ ), the high coordination number of Ln 3+ , and the dynamic properties of Ln 3+ Ligands.…”
Section: Self-healing Mechanism Based On Metal Bondmentioning
confidence: 99%
“…Therefore, it is imperative to procure a rapid, less-consumed, and easy-to-use method to identify and respond to methanol or its vapor. Optical sensors have attracted extensive attention owing to technical simplicity, high sensitivity, and efficiency. , A variety of materials for fluorescence sensors have been developed, including inorganic nanomaterials, quantum dots, organic molecules, and luminescent metal–organic hybrid materials (LMOHs). Among them, LMOHs constituted by bridging central metal ions or metal clusters with organic ligands have the characteristics of both inorganic and organic materials which have been widely applied in sensor, optics, and bioimaging fields on account of flexible synthesis strategies, good porosity, large specific surface area, appropriate biocompatibility, non-aggregating quenching, and excellent photoluminescence (PL) properties. Luminescent supramolecular metallogels, as an emerging class of LMOHs, are gradually being favored by researchers due to the characteristics of both gels and LMOHs. , Remarkably, the gel characteristics endow a qualitative breakthrough in the viscosity, flexibility, ductility, and self-repair of the metallogel. Therefore, luminescent supramolecular metallogels have great potential in assembling optical devices, designing optical probes, and constructing fluorescent sensors.…”
Section: Introductionmentioning
confidence: 99%